The Importance of Phosphates for DNA G‐Quadruplex Formation: Evaluation of Zwitterionic G‐Rich Oligodeoxynucleotides. (13th May 2020) - Su, Yongdong; Edwards, Patrick J. B.; Stetsenko, Dmitry A.; Filichev, Vyacheslav V.
Abstract: A quaternary ammonium butylsulfonyl phosphoramidate group (N+) was designed to replace all the phosphates in a G‐rich oligodeoxynucleotide d(TG4 T), resulting in a formally charge‐neutral zwitterionic N+TG4 T sequence. We evaluated the effects of N+phosphate modifications on the structural, thermodynamic and kinetic properties of the parallel G‐quadruplexes (G4) formed by TG4 T and compared them to the properties of the recently published phosphoryl guanidine d(TG4 T) (PG‐TG4 T). Using size‐exclusion chromatography, we established that, unlike PG‐TG4 T, which exists as a mixture of complexes of different molecularity in solution, N+TG4 T forms an individual tetramolecular complex. In contrast to PG modifications that destabilized G4s, the presence of N+ modifications increased thermal stability relative to unmodified [d(TG4 T)]4 . The initial stage of assembly of N+TG4 T proceeded faster in the presence of Na + than K + ions and, similarly to PG‐TG4 T, was independent of the salt concentration. However, after complex formation exceeded 75 %, N+TG4 T in solution with Na + showed slower association than with K + . N+TG4 T could also form G4s in solution with Li + ions at a very low strand concentration (10 μM); something that has never been reported for the native d(TG4 T). Charge‐neutral PG‐G4s can invade preformed native G4s, whereas no invasion was observed between N+and native G4s, possibly due to the increased thermal stability of [N+TG4 T]4 . The N+ modification makes d(TG4 T) fully resistant to enzymatic digestion, which could be useful for intracellular application of N+‐modified DNA or RNA. Abstract : Native negatively charged DNA strands exhibit slow formation of intermolecular G‐quadruplexes. In contrast, a modified TG4 T sequence in which each phosphate is replaced with a zwitterionic moiety assembles much faster in both Na + ‐ and K + ‐containing buffers, shows increased thermal stability and great resistance against exonucleases.